Ian Campbell: Ethiopia 1937: The Plot to Kill Graziani. The Attempted Assassination of Mussolini’s Viceroy (Aethiopica, 2013)
Review
Keywords: History; Italian Occupation; Military; Politics; Graziani; Massacre